SPANNING THE GAP BETWEEN DEAF AND HEARING WORLDS - Absamatova Gulkhayo Bakhodirovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Sign interpreting plays a decisive role in facilitating communication between deaf and hearing individuals. As a professional and linguistic practice, it ensures equitable access to education, employment, healthcare, and public participation for members of the Deaf community. This article explores the historical evolution, linguistic principles, cognitive demands, ethical standards, and modern challenges in the field of sign interpreting. It also highlights the cultural significance of Deaf identity and the emerging impact of technological advancements, such as video remote interpreting (VRI) and artificial intelligence-driven tools. Drawing from research in linguistics, psychology, and communication studies, the article argues that sign interpreting is more than a process of language translation; it is a complex act of intercultural mediation requiring professionalism, empathy, and cultural competence. Finally, it presents recommendations for the advancement of interpreter education, technology integration, and inclusive policies to ensure communication equality.